2016 11th International Conference on Availability, Reliability and Security (ARES) 2016
DOI: 10.1109/ares.2016.48
|View full text |Cite
|
Sign up to set email alerts
|

Towards a CDS-based Intrusion Detection Deployment Scheme for Securing Industrial Wireless Sensor Networks

Abstract: Abstract-The use of wireless communication is a major trend in the so called Supervisory Control and Data Acquisition systems (SCADA). Consequently, Wireless Industrial Sensor Networks (WISN) were developed to meet real time and security requirements needed by SCADA systems. In term of security, WISN suffer from the same threats that those targeting classical WSN. Indeed, attackers mainly use wireless communication as a medium to launch these attacks. But as these networks are used to manage critical systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Olawumi et al showed three types of effective attacks, using vulnerabilities of the Zigbee standard, and proposed countermeasures against them. Alcaraz and Lopez [15] and Bayou et al [16] applied threat models of other networks to the IWSN. Alcaraz and Lopez analyzed the application of the supervisory control and data acquisition (SCADA) threat model and the WSN threat model in Zigbee, WirelessHART, and ISA 100.11a network environments and proposed countermeasures.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Olawumi et al showed three types of effective attacks, using vulnerabilities of the Zigbee standard, and proposed countermeasures against them. Alcaraz and Lopez [15] and Bayou et al [16] applied threat models of other networks to the IWSN. Alcaraz and Lopez analyzed the application of the supervisory control and data acquisition (SCADA) threat model and the WSN threat model in Zigbee, WirelessHART, and ISA 100.11a network environments and proposed countermeasures.…”
Section: Related Workmentioning
confidence: 99%
“…In order to apply the IWSN standard to industrial control systems, security for the IWSN is essential. Therefore, many studies have been carried out to identify vulnerabilities through security analysis of the IWSN standard and to find countermeasures [11,12,13,14,15,16,17]. While it is true that the security of the IWSN standard has been strengthened through these studies, there is still a lack of study on the provisioning process, which is where all security begins.…”
Section: Introductionmentioning
confidence: 99%
“…The deployment of IDS-agents is out of the scope of this paper. However, in our study, we use the scheme proposed in [14]. This scheme uses the graph theory concept of Connected Dominated Set to ensure the gathering of the whole exchanged traffic.…”
Section: Ids-agents Deployment Schemementioning
confidence: 99%
“…∧is_packetT ype(packet , Ack) ∧ is_dstAddr(packet , s) ∧is_assignedF q(s, packet) ∧ is_slotStartT ime(s, packet) (14) We should note that the Network Manager is responsible of building, managing and updating slots and frequencies planning.…”
Section: Communication Scheduling Rulesmentioning
confidence: 99%